2012
DOI: 10.1002/jobm.201200060
|View full text |Cite
|
Sign up to set email alerts
|

Bio-based nanoemulsion formulation, characterization and antibacterial activity against food-borne pathogens

Abstract: The current study deals with the formulation and characterization of bio-based oil in water nanoemulsion and its potential antibacterial activity. A typical v/v% of eucalyptus oil (16.66%), Tween 80 (16.66%), and water (68.68%) was prepared by ultrasonication method. The mean droplet size was 17.1 nm as confirmed by dynamic light scattering. Different concentrations of the formulation ranging from undiluted to 10-, 100-, and 1000-fold dilutions were used to check the antibacterial activity in three different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…[12][13][14] There is a growing interest in food and beverage industries for the utilization of nanoemulsion as a colloidal system for delivery of bioactive components such as antimicrobials, colors, flavours, micronutrients and nutraceuticals. [15][16][17][18][19] The applications of nanoemulsions as attractive systems has gained interest nowadays due to their unique properties such as extremely small droplet diameter in the range of 20-200 nm, [20] high physical stability, high bioavailability and optical transparency compared with other conventional emulsions. [21] Previous studies showed encapsulation of essential oils into emulsion due to the hydrophobic nature of oil this leads to higher solubility and dispersibility in aqueous media and also to reduce organoleptic properties in the food system.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] There is a growing interest in food and beverage industries for the utilization of nanoemulsion as a colloidal system for delivery of bioactive components such as antimicrobials, colors, flavours, micronutrients and nutraceuticals. [15][16][17][18][19] The applications of nanoemulsions as attractive systems has gained interest nowadays due to their unique properties such as extremely small droplet diameter in the range of 20-200 nm, [20] high physical stability, high bioavailability and optical transparency compared with other conventional emulsions. [21] Previous studies showed encapsulation of essential oils into emulsion due to the hydrophobic nature of oil this leads to higher solubility and dispersibility in aqueous media and also to reduce organoleptic properties in the food system.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The antimicrobial oil-in-water nanoemulsion was shown to possess a broad spectrum of activity against bacterial pathogens due to the reduced droplet diameter. 11,12 Recently, by our group, the ultrasonic emulsification of eucalyptus oil nanoemulsion was studied, and size reduction was achieved with the aid of ultrasonication time. Also, the stabilized emulsion system was studied for topical application against S. aureus by in vitro and was shown to be nonirritant, and high wound healing activity was observed in Wistar rats in an in vivo experiment.…”
Section: Introductionmentioning
confidence: 99%
“…PDI value provides information about the distribution of particle size, being the indicated value <0.3, as in the present study. The zeta potential, which reflects the surface charge of a nanostructure, had negative results in all nanostructures used in the tests, which was expected, as it was used a negatively charged surfactant (Sugumar et al., ; Sun et al., ). The pH of both nanoemulsions and solid lipid nanoparticles presented results between 4.0 and 5.9.…”
Section: Discussionmentioning
confidence: 82%